The effect of institutionalization level on the relationship of corporate governance with money laundering activity: An example of the BIST Corporate Governance Index - Cemberci, Murat; Basar, Dogan; Yurtsever, Zuhal (ELSEVIER, 2022)
The goal of this study is to analyze the impact of corporate governance (CG) principles on perceptions of anti-money-laundering effectiveness (AMLE) based on data obtained from financial institutions that are and are not included in the Borsa Istanbul (BIST) Corporate Governance Index (CGI). This study examines the relationship between CG and perceptions of AMLE through a survey of participants working at financial in-stitutions, divided into two groups, conducted in April 2021. The results from testing the hypotheses show a significant relationship between CG and AMLE across multiple subdimensions. However, in terms of the perceptions of AMLE, it is not found a significant difference between financial institutions based on whether they are included in the BIST CGI.Copyright (c) 2022 Borsa Istanbul Anonim S , irketi. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Anti-money laundering effectiveness; BIST CGI; Turkey; Business & Economics